Increased fibroblast metabolic activity of collagen scaffolds via the addition of propolis nanoparticles - González Masís, Jeimmy (2020)
Se seleccionó la licencia Creative Commons para este envío. El documento trae lo siguiente: © 2020 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/)